Low-Energy Collisions of Protonated Enantiopure Amino Acids with Chiral Target Gases - Kulyk, K.; Rebrov, O.; Ryding, M.; Thomas, R. D.; Uggerud, E.; Larsson, M. (Journal of the American Society for Mass Spectrometry, 2017)
Here we report on the gas-phase interactions between protonated enantiopure amino acids ( l - and d -enantiomers of Met, Phe, and Trp) and chiral target gases [( R )- and ( S )-2-butanol, and ( S )-1-phenylethanol] in 0.1–10.0 eV low-energy collisions. Two major processes are seen to occur over this collision energy regime, collision-induced dissociation and ion-molecule complex formation. Both processes were found to be independent of the stereo-chemical composition of the interacting ions and targets. These data shed light on the currently debated mechanisms of gas-phase chiral selectivity by demonstrating the inapplicability of the three-point model to these interactions, at least under single collision conditions. Graphical Abstract